Pengembangan Pemberdayaan dan Demonstrasi Skill Menu “Diet Rendah Garam” pada Penderita Hipertensi - Suharno Usman; Anshar Rante; Djusmadi Rasyid (Universitas Mathla'ul Anwar Banten, 2021)
DEVELOPMENT OF EMPOWERMENT AND DEMONSTRATION OF “LOW SALT DIET” MENU SKILL ON PATIENTS WITH HYPERTENSION. There are 60% of people with hypertension ending in stroke, while the rest in blindness, kidney failure, and various heart diseases. JNC-8 recommends limiting high intake of salt as one of the preventions of hypertension. Public facilities or facilities especially health facilities are still minimal, health personnel are still lacking, internet access is very limited, making To'bungku village, Banggai Islands less updated on health information related to education or counseling and health empowerment training about